Bimbingan Konseling Islam Melalui Teknik Self Management untuk Meningkatkan Pemanfaatan Waktu Luang pada Remaja Putus Sekolah - Rahayu, Citra Repsi Tri; Kusnadi, Kusnadi; Rasmanah, Manah (Journal of Society Counseling, 2023)
This research aims to determine Islamic counseling guidance through self-management techniques in increasing the use of free time among out-of-school teenagers (R clients) in Daya Makmur Village, Muara Padang District, Banyuasin Regency. The main subject in this research is client "R" who is the primary data source. Meanwhile, secondary research data sources are the client's father, the client's mother, the client's younger sibling, and the client's friends. The method used is a qualitative research method with a case study approach. The data collected through observation, interviews, and documentation. The data analysis technique used is the Robert K. Yin model consisting of 3 techniques, namely pattern matching, data explanation, and time series analysis. The research results analyzed in three stages, namely the initial stage, the core stage, and the final stage. The core stage is the process of providing self-management techniques, which includes several phases, namely self-monitoring, positive reinforcement (reward), contract or agreement with yourself (self-contracting), and mastery of stimuli (stimulus control), after implementation. Islamic counseling guidance through self-management techniques shows that client "R" experienced quite positive improvements where there is new behavioral changes by client "R".